A study on factors in term of consumer behavior in buying residential property in Johor Bahru, Johor / Mohamed Noor Hafidz Md Othman - Md Othman, Mohamed Noor Hafidz (Faculty of Business and Management, 2011)
The term consumer behaviour is defined as the behaviour that consumers display in searching for, purchasing, using, evaluating, and disposing of products and services that they expect will satisfy their needs. Consumer behaviour focuses on how individuals make decisions to spend their available resources (time, money, effort) on consumption-related items. That includes what they buy it, why they buy it, when they buy it, where they buy it, how often they buy it, how often they use it, how they evaluate it after the purchase, the impact of such evaluations on future purchases, and how they dispose of it. Clearly, as individuals, we are all unique. However, one of the most important constants among all of us, despite our differences, is that, above all, we are consumers. Due to this statement, researcher feels exuberant to conduct a study to measure the Consumer Behavior in Buying Residential Property in Johor Bahru, Johor. The independent variables of this study were the consumer behavior dimensions which are group influences, Individual/ Psychological Influences, and Marketing Mix while the dependent variables are the Factor Influencing Buyer’s Decision Making. As for the instrument to find the result of the study, researcher used SPSS Version 14 and Paired T-test to testing the hypotheses. The findings of this study will give the benefits to UDA Land (South) Sdn Bhd to improve their consumer behaviour and try to win the customers heart and loyalty.